Cerebral hemodynamics during graded Valsalva maneuvers - Perry, Blake G.; Cotter, James D.; Mejuto, Gaizka; Mündel, Toby; Lucas, Samuel J. E. (Frontiers in Physiology, 2014)
The Valsalva maneuver (VM) produces large and abrupt changes in mean arterial pressure (MAP) that challenge cerebral blood flow and oxygenation. We examined the effect of VM intensity on middle cerebral artery blood velocity (MCAv) and cortical oxygenation responses during (phase I, II, III) and following (phase IV) a VM. Healthy participants (n=20 mean ± SD: 27±7 y) completed 30 and 90% of their maximal VM mouth pressure for 10 s (order randomised) whilst standing. Beat-to-beat MCAv, cerebral oxygenation (NIRS) and MAP across the different phases of the VM are reported as the difference from standing baseline. There were significant interaction (phase * intensity) effects for MCAv, total oxygenation index (TOI) and MAP (all P<0.01). MCAv decreased during phases II and III (P<0.01), with the greatest decrease during phase III (-5 ± 8 and -19 ± 15 cm•s-1 for 30 and 90% VM, respectively). This pattern was also evident in TOI (phase III: -1±1 and -5±4%, both P<0.05). Phase IV increased MCAv (22±15 and 34±23 cm•s-1), MAP (15±14 and 24±17 mm Hg) and TOI (5±6 and 7±5 %) relative to baseline (all P<0.05). Cerebral autoregulation, indexed, as the %MCAv/%MAP ratio, showed a phase effect only (P <0.001), with the least regulation during phase IV (2.4±3.0 and 3.2±2.9). These data illustrate that an intense VM profoundly affects cerebral hemodynamics, with a reactive hyperemia occurring during phase IV following modest ischemia during phases II and III.